Deficiency in endocannabinoid synthase DAGLB contributes to early onset Parkinsonism and murine nigral dopaminergic neuron dysfunction - Zhenhua Liu; Nannan Yang; Jie Dong; Wotu Tian; Lisa Chang; Jinghong Ma; Jifeng Guo; Jieqiong Tan; Ao Dong; Kaikai He; Jingheng Zhou; Resat Cinar; et al. (Nature Communications, 2022)
2- arachidonoylglycerol (2-AG), an abundant endocannabinoid in the brain, regulates diverse neural functions. Here, the authors identified four loss-of-function mutations in dicylglycerol lipase β (DAGLB) from six patients with early onset Parkinsonism. In mice, loss of DAGLB in dopamine neurons reduced neuronal activity and impaired locomotor function and augmentation of 2-AG levels boosted neuronal activity and rescued locomotor deficits.